Characterization of the native form and the carboxy‐terminally truncated halotolerant form of α‐amylases from Bacillus subtilis strain FP‐133. (16th February 2015) - Takenaka, Shinji; Miyatake, Ayaka; Tanaka, Kosei; Kuntiya, Ampin; Techapun, Charin; Leksawasdi, Noppol; Seesuriyachan, Phisit; Chaiyaso, Thanongsak; Watanabe, Masanori; Yoshida, Ken‐ichi
<x xml:space="preserve">Abstract</x> Two amylases, amylase I and amylase II from Bacillus subtilis strain FP‐133, were purified to homogeneity and characterized. Their stabilities toward temperature, pH, and organic solvents, and their substrate specificities toward polysaccharides and oligosaccharides were similar. Under moderately high salt conditions, both amylases were more stable than commercial B. licheniformis amylase, and amylase I retained higher amylase activity than amylase II. The N‐terminal amino acid sequence, genomic southern blot analysis, and MALDI‐TOFF‐MS analysis indicated that the halotolerant amylase I was produced by limited carboxy‐terminal truncation of the amylase II peptide. The deduced amino acid sequence of amylase II was >95% identical to that of previously reported B. subtilis α‐amylases, but their carboxy‐terminal truncation points differed. Three recombinant amylases — full‐length amylase corresponding to amylase II, an artificially truncated amylase corresponding to amylase I, and an amylase with a larger artificial C‐terminal truncation — were expressed in B. subtilis. The artificially truncated recombinant amylases had the same high amylase activity as amylase I under moderately high salt conditions. Sequence comparisons indicated that an increased ratio of Asp/Glu residues in the enzyme may be one factor responsible for increasing halotolerance.